(untitled) (Hilo Analítico, 2023)
The approach and start of a therapy from the systemic approach transcends whoever receives that orientation and interacts indirectly or directly in some cases, in order to identify, assess and determine actions for the improvement in these networks or support nuclei; For this, it is necessary to clearly contextualize the bases and beginning of the family and closest members, since to a large extent they can be the cause of the discomforts reflected or their possible treatment.